Understanding food addiction through the lens of psychological well-being, self-control, and eating behavior: a cross-sectional study - Acik, Murat; Ulger, Taha Gokmen (Bmc, 2025)
Objective This study aimed to elucidate how psychological distress, self-control, and sustainable healthy eating behaviors interact to shape food addiction, by simultaneously modeling their direct and indirect effects in adult population. Methods A cross-sectional survey was conducted with 985 adults (mean age: 28.8 +/- 10.9) from community health centers in Elaz & imath;& gbreve;, Turkey. Standardized instruments measured depression, anxiety, stress (DASS-21), self-control, sustainable healthy eating, and food addiction (YFAS). Statistical analyses included logistic regression and structural equation modeling (SEM). Results Food addiction prevalence was 34.9%. Individuals with food addiction had significantly higher mean depression, anxiety, and stress scores, and lower self-control (37.1 +/- 4.3 vs. 40.2 +/- 4.3, p < 0.001) and sustainable healthy eating scores (15.0 +/- 3.9 vs. 17.6 +/- 4.7, p < 0.001) compared to those without addiction. Logistic regression indicated that anxiety (OR[95% CI] = 1.27 [1.20-1.34]) was the strongest predictor, while higher self-control (OR = 0.92[0.88-0.95]) and sustainable eating (OR = 0.94[0.90-0.97]) reduced risk. The final model explained 44% of the variance. SEM showed that self-control and sustainable eating behaviors significantly mediated the relationship between stress and food addiction. Discussion Anxiety exerts the strongest direct influence on food addiction, while self-control and sustainable dietary habits serve as key mediators, particularly in the stress-food addiction pathway. These findings underscore the need for multidimensional interventions that integrate psychological and behavioral strategies to effectively prevent and manage food addiction.
Keywords: Food addiction; Anxiety; Stress; Depression; Self-control; Sustainable eating